An optimized sliding rail-assisted micrometer system for sensing volume measurement of open-ended coaxial probes in breast cancer dielectric property analysis - Chen, Shuai; Lu, Zhongliang; Huang, Qiang; Zhao, Gaowei; Sun, Zheng; Zhou, Jing; Liao, Yupeng (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveThe open-ended coaxial probe (OECP) method has demonstrated promising potential in biological tissue measurements. However, it still faces challenges such as significant measurement errors and poor repeatability. Research indicates that a substantial portion of these errors originates from tissue heterogeneity. To mitigate errors associated with tissue heterogeneity and accurately interpret the relationship between the dielectric properties and histology of heterogeneous tissue samples, detailed knowledge of the probe’s effective sensing volume is essential.MethodsIn this study, the effective sensing volumes of two commonly used small-aperture probes (with diameters of 2.20 mm and 3.58 mm) were measured. The vertical sensing volume is represented by the sensing depth, while the horizontal sensing volume is characterized by the sensing radius. A measurement model for the sensing volume of the OECP method was established using a heterogeneous dielectric property layered model combined with an optimized sliding rail-assisted micrometer system. Dielectric property bilayer models were constructed using materials with distinct dielectric parameters (Teflon, ethanol, methanol, deionized water) and biological tissue simulants (dimethyl sulfoxide, salt-sugar mixed solution). To validate the sensing volume derived from the aforementioned bilayer model, we conducted experimental measurements on porcine tissue and human breast tissue, both of which exhibit well-defined layered structures. In this experiment, the geometric center of a Teflon cube was designated as the origin for probe movement.ResultsThe measured sensing depth ranges were 0.44 to 0.62 mm for a 2.20 mm diameter probe and 0.75 to 0.98 mm for a 3.58 mm diameter probe. While the corresponding sensing radius ranges of 0.36 to 0.63 mm for the 2.20 mm diameter probe and 0.71 to 0.99 mm for the 3.58 mm diameter probe.ConclusionThe results indicate that both the sensing depth and radius of the probe increase significantly with larger coaxial probe aperture sizes. Furthermore, a smaller aperture reduces the influence of tissue heterogeneity on measurements, while the effective sensing volume remains consistent across frequencies.